Implementation of Sustainable Human Resource Management at the MSME CV. Wirajaya Mandiri Stationery in Batam City - Dhita Hafizha Asri; Dessi Angelica; Lichi Zesliyana; Serly Diana; Alex Putra Pranata; Frento Frento (NuCSJo : Nusantara Community Service Journal, 2025)
MSMEs play a crucial and strategic role in national economic development. In addition to contributing to economic growth and employment, MSMEs also play a crucial role in the distribution of various development outcomes. In today's digital era, stationery remains crucial in office operations. The focus of this study is CV. Wirajaya Mandiri Stationery, a stationery (ATK) business located in the Mitra Raya Ruko Complex, Block B-05, Batam Center, and has been operating since 2007. The purpose of this study is to determine and analyze the implementation of human resource management at one MSME in Batam City. This research can serve as an evaluation for MSME owners in analyzing and optimizing their human resource management practices, thereby increasing productivity, efficiency, and business sustainability. The analysis shows that HRM elements such as job analysis, recruitment, performance appraisal, training and development, and compensation and benefits have been implemented functionally.